2023
DOI: 10.1080/13510002.2023.2224607
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MEG3 ameliorates cardiomyocyte apoptosis and autophagy by regulating the expression of miRNA-129-5p in a mouse model of heart failure

Abstract: The long non-coding RNA, maternally expressed gene 3 (MEG3), are involved in myocardial fibrosis and compensatory hypertrophy, but its role on cardiomyocyte apoptosis and autophagy in heart failure (HF) remains unclear. The aim of this study was to investigate the effect of MEG3 on cardiomyocyte apoptosis and autophagy and the underlying mechanism. A mouse model of HF was established by subcutaneous injection of isoproterenol (ISO) for 14 days, and an in vitro oxidative stress injury model was replicated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
2
0
1
Order By: Relevance
“… 2 A apoptose de cardiomiócitos causa a perda de cardiomiócitos e leva à baixa contratilidade miocárdica. 3 Evidências crescentes indicam que a apoptose de cardiomiócitos atua como um fator chave no agravamento da IC, e a supressão do remodelamento ventricular causado pela apoptose de cardiomiócitos pode melhorar o prognóstico de pacientes com IC. 4 Assim, uma melhor compreensão do mecanismo subjacente à apoptose de cardiomiócitos na IC pode ajudar a identificar novos alvos e desenvolver estratégias mais eficazes para o tratamento da IC.…”
Section: Introductionunclassified
See 1 more Smart Citation
“… 2 A apoptose de cardiomiócitos causa a perda de cardiomiócitos e leva à baixa contratilidade miocárdica. 3 Evidências crescentes indicam que a apoptose de cardiomiócitos atua como um fator chave no agravamento da IC, e a supressão do remodelamento ventricular causado pela apoptose de cardiomiócitos pode melhorar o prognóstico de pacientes com IC. 4 Assim, uma melhor compreensão do mecanismo subjacente à apoptose de cardiomiócitos na IC pode ajudar a identificar novos alvos e desenvolver estratégias mais eficazes para o tratamento da IC.…”
Section: Introductionunclassified
“… 2 Cardiomyocyte apoptosis causes the loss of cardiomyocytes and leads to poor myocardial contractility. 3 Mounting evidence has indicated that cardiomyocyte apoptosis acts as a key factor in the aggravation of HF, and suppression of ventricular remodeling caused by cardiomyocyte apoptosis can improve the prognosis of patients with HF. 4 Thus, a better understanding of the underlying mechanism of cardiomyocyte apoptosis in HF may help to identify new targets and develop more effective strategies for HF treatment.…”
Section: Introductionmentioning
confidence: 99%
“… 6) LncRNA MEG3 is involved in cardiomyocyte autophagy and cardiac fibrosis, and silencing of lncRNA MEG3 ameliorated cardiac hypertrophy via the miRNA-129-5p/ATG14/Akt pathway in a mouse model. 7) A transcription factor ETS2 modulated the lncRNA TUG1/miR-1205p/ATG7 axis to promote heart failure progression by inducing cell apoptosis and autophagy. 8) …”
mentioning
confidence: 99%